Collaborative Robotic Environment for Educational Training in Industry 5.0 Using an Open Lab Approach. Issue 17 (2022) - Pozo, Esteban; Patel, Nikunjkumar; Schrödel, Frank
Abstract: This paper focuses on the laboratory setup that enables modern education concepts related to collaborative robotics. This facility is meant to be an open lab environment where the access is free and all the necessary resources are available. We explain how a safe environment for collaborative robotics is created by using combined technologies such as haptics and vision systems, which are expected to play a major role in the assembly lines of industry 5.0. The goal of this paper is to provide a safe collaborative environment where experiments related to control engineering, artificial intelligence, robotic vision, haptics and sensor engineering can take place.